The evaluation of cooling systems to reduce heat strain in individuals wearing personal protective clothing - Bach, A. J. E. (Queensland University of Technology, 2020)
Personal cooling systems, worn by emergency first responders under protective clothing, are designed to minimise the risk of heat illness. This thesis reaffirms that first responder agencies (e.g. fire, police) identify heat illness as a genuine threat to worker safety. Further, it identifies that certain personal cooling systems alleviate the heat better than others, and the combination of air temperature and humidity has a direct effect on their performance. Therefore, the use of cooling systems, by first responder agencies, needs to be considered in the context of the protective clothing being worn and the environment encountered.